The Influence of Brand Image, Brand Trust and Marketing Strategy on Motorcycle Purchase Decisions - Innesense Ave Djatajuma; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the influence in the independent variables of this study in the form of brand image variables, brand trust variables and marketing strategy variables on the dependent variables of this study in the form of variable of purchasing decisions on Honda Beat motorcycles. The method in this study is descriptive-quantitative with a population of respondents or more specifically consumers of Honda Beat motorcycles. The sample of respondents to the study was 100 with purposive sampling techniques. In using the purposive sampling technique, it is expected that the sample is in accordance with the requirements or criteria needed in this study. The data used was in the form of primary data by distributing questionnaires with model tests in the form of multiple linear regressions processed using SPSS 25. The results were found after analysis using processed data with the following conclusions that brand image, brand trust and marketing strategy have a positive and significant effect on purchasing decisions. Previously tested against question items that were declared valid and reliable.